Effects of supplementary LED light on the growth of lettuce in a smart hydroponic system - Thinley Namgyel (2019)
© 2018 IEEE. Leveraging LED lighting technology and hydroponic culture technique in urban agriculture have recently become promising solution to ecologically unfriendly, conventional farming practices that need high energy and water consumption. In this study, we have investigated the response of lettuce plant (Latuca sativa butterhead) to the irradiance of different supplemental LED light in comparison to plants cultured under only natural light. Lettuce plants were treated with blue LEDs (440-450 nm), red LEDs (640-660 nm), red LED (640-660 nm) + blue LED (440-450 nm) with a ratio of (1:1). Lettuce plants were cultured hydroponically and provided 16 h photoperiod at average air temperatures of 35.87/31.3 °C (day/night) and 76 % humidity for 50 days. Greater accumulation of biomass in plants treated with the blue LED light as compared to the other treatments was observed. Plants cultivated under irradiation of LED light yielded higher number of leaves/plant, superior leaf area and healthy appearance. It is evident that supplementary LED light positively effects the lettuce plants in its growth and morphology. Hence, supplementary LED lighting technology has demonstrated beneficial and suitable in the outdoor hydroponic system for the lettuce production.